Sustainability Reporting as a Catalyst: Investigating the Mediating Path Between Corporate Characteristics and SDGs - Ifada, Luluk Muhimatul; Chafsya, Lathfia Arrosikha (Accounting Analysis Journal, 2025)
Purpose: This research examines how LQ45 companies in Indonesia support sustainable practices by disclosing their SDGs. Method: The method used is a panel data regression method: random effect. Using 131 samples unbalanced panel data from 2019 to 2022, this research uses 17 SDGs developed by the UN as its SDGs disclosure index. Findings: The results show that LQ45 companies in Indonesia contribute more through company activities in accordance with SDG 8. This research also shows that SDGs disclosure gradually increased during the research sample period. In addition, this research finds that firm age and sustainability reporting have a positive influence on SDGs disclosure, while firm size does not affect SDGs disclosure. Novelty: The research using Sustainability Reporting as a mediation to find the most effective strategy towards SDGs. This research also fulfilling the lack of empirical research on SDGs in developing countries since SDGs have become a global concern recently.